(untitled) (CIPEEX, 2025)
Objective: This study aimed to determine the prevalence of falls among elderly individuals in the community with hypertension and diabetes mellitus. Methods: This is a cross-sectional, descriptive, and quantitative study that evaluated economic and sociodemographic aspects, general health, level of frailty, and functional autonomy of elderly people. The sample consisted of 110 elderly individuals (n=110) who met the inclusion criteria and agreed to participate. Results: It was found that 38.2% (n=42) of elderly patients with hypertension and diabetes mellitus suffered falls in the last twelve months, and 21.8% (n=24) reported having suffered only one fall in that period. The results also indicate that 36.84% of elderly patients with diabetes mellitus and 50% of elderly patients with hypertension reported falls in the last twelve months, showing a considerable prevalence of these occurrences in this group. Conclusion: Although preventive actions have reduced the number of falls, it is important to continue focusing on strategies to further decrease this prevalence and improve the quality of life of the elderly.